The Eligibility of Commercial Companies and the Relationship of the Subject of the Company with it in the Laws of Iran, Egypt, and Lebanon - Fatemeh Rajaei (پژوهشهای حقوقی)
The specific characteristics of legal entities, including commercial companies, have made them distinct from natural persons and their capacity deffers from natural persons. Determining the scope of a commercial company's is important because it determine the company capacity and scope of the company rights and duties and the powers of its members (general assemblies, board of directors, etc). There are two views on this issue in the Iranian legal system; some limit the company's capacity to its scope, but others do not consider the scope of the company to be a limiting factor of the company's capacity and believe that the company has a general capacity. This paper firstly studies the company's capacity in Iranian regulations and then, compare it with the Egypt and Lebanon regulations, and finally concludes that in these countries, companies have a full capacity and their capacity did not limit to the scope of the company.